Digital Video For Dummies, Third Edition - Underdahl, Keith (Wiley Publishing, 2011)
Digital media sales represent a growing market in consumer technology; in previous editions, this book has been the top-selling reference for digital video beginners Fully revised and completely focused on consumer digital video users and editors who have little to no experience with the equipment Walks readers through the basics of selecting equipment, installing software and hardware, shooting good video, getting files into a PC, editing, and outputting to the Internet, videotape, or a DVD